Exploring the Mindset of Wonosari Village Citizens in the Mantra of the Grebeg Memetri Tradition, Tutur District, Pasuruan District (Ethnosemiotic Study) - Mardiana, Ninik; Andharu, Devito; Fadillah, M Reza Ishadi; Setyawan, Dedi (CV. Tripe Konsultan, 2024)
In the Pasuruan Regency of East Java Province, specifically in the Tutur Subdistrict, there is a village called Wonosari that holds a unique traditional ceremony to honor God, seek His blessings, and request safety from disasters for the village. The villagers of Wonosari conduct this traditional ceremony, which involves oral literature in the form of mantras. The mantras used in this tradition serve as prayers and are recited during the ritual burial of a cow's head in the center of the market. The mantras are recited by the village elders or traditional shamans during the ceremony. During the execution, the mantras are chanted aloud and listened to by the villagers of Wonosari in a solemn atmosphere.The traditional ritual of burying a cow's head in the village of Wonosari is known as Grebeg Memetri. The term